Avaliação genética em abelhas Apis mellifera africanizadas para produção de geléia real - Faquinello, Patrícia (2007)
This research was carried out to estimate parameters to establish breeding programs in Africanized honey bees for royal jelly production. It was used 15 mother queens that supplied larvae for rearing their daughters. After emersion the queens were anesthetized and made measures for body weight (mg) length and width of the wing and abdomen (cm). The queens were selected for body weight and introduced in honeybee hives where there production was measured. The analyzed production traits were: acceptance percentage (%), royal jelly production per colony (g), royal jelly production per cup (mg) and pollen supplement intake (g). The data were submitted to unicaracter and multicaracter analysis using the bayesian inference. The average obtained for selected queens were 209.34 mg for queen weight, 1.00 and 0.37 cm for wing length and width, 1.10 and 0.46 cm for abdomen length and width, respectively. The heritability estimates, in bicaracter analysis, for production and morphometric traits were 0.49 for royal jelly production per colony, 0.65 for body weight, 0.55 and 0.55 for wing length and width, 0.59 and 0.57 for abdomen length and width, respectively. The heritability estimative for production traits, in bicaracter analysis, were from low to high ranging from 0.10 to 0.55. The genetic correlation data, in a general way, was higher to phenotypic data. In conclusion, the selection for abdomen width trait can produce better genetic earnings. Evaluating three situations through selection efficiency, in comparison to selection for royal jelly production per colony, the selection of royal jelly production per colony is recommended.